Assessment in the English Curriculum at Islamic Higher Education: Policy, Instruments, and Pedagogical Realities - Habibie, Alvons; Talib, Rasuna (Irfani, 2026)
This study aims to analyze how English lecturers at the Department of English Education (Tadris Bahasa Inggris), IAIN Sultan Amai Gorontalo interpret and implement authentic assessment in the context of language learning, and to identify the challenges encountered in its application. Employing a qualitative descriptive approach with an interpretive strategy, data were obtained through in-depth interviews, classroom observations, and document analysis. The findings reveal that lecturers' understanding of authentic assessment remains varied, influenced by teaching experience, pedagogical literacy, and the absence of complete institutional guidelines. Assessment practices in the classroom have shown efforts toward process-based approaches through revision and reflection activities, yet they remain dominated by conventional product-oriented evaluation. The main obstacles identified include lecturers' workload, lack of assessment training, and limited institutional support. This study underscores the importance of policy alignment between curriculum policy and field practice, including the provision of training, shared rubrics, and assessment moderation systems. Conceptually, these findings extend understanding of authentic assessment in Islamic higher education, demonstrating that its success is determined not only by technical assessment design, but also by shifts in pedagogical paradigms and institutional culture that support reflective and contextual learning.